Resveratrol, from experimental data to nutritional evidence: the emergence of a new food ingredient. (15th July 2013) - Raederstorff, Daniel; Kunz, Iris; Schwager, Joseph
Abstract : The polyphenol resveratrol is found notably in grapes and in a variety of medicinal plants. Recently, resveratrol has been suggested to have cardioprotective effects and to improve metabolic health by mimicking the effects of calorie restriction. Numerous animal and in vitro studies suggest that resveratrol could improve cardiovascular and metabolic health in humans. In view of this compelling preclinical evidence, several human studies investigating the effects of resveratrol on vascular and metabolic health have been initiated. Collectively, the animal, human epidemiological, and first human intervention studies support a role of resveratrol in vascular and metabolic health. This has led to the introduction of the first supplement and food products containing resveratrol and its emergence as a promising new health ingredient. Thus, supplementation with resveratrol may be included in nutritional and lifestyle programs aiming to reduce the risk of vascular and obesity‐related problems.